2006
DOI: 10.2174/138920006774832578
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Pharmacodynamics: A Complicated Relationship

Abstract: With few exceptions, drugs exert their effects not within the plasma compartment, but in the defined target tissues. The process of drug distribution to the active site constitutes the "link-bridge" of the pharmacokinetic/pharmacodynamic (PK/PD) relationship. In spite of the importance of drug distribution as a key factor in determining pharmacologic response, research on drug distribution has historically received much less attention than that of absorption, metabolism, and excretion. The negligence of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 192 publications
(280 reference statements)
0
39
1
Order By: Relevance
“…Agents like ethanol, cyclosporine, and morphine have been identified to be so affected, in which the GI mucosa and the liver remove a significant portion of a toxicant during its passage through these tissues, thereby reducing its systemic availability. According to Lim et al[15], ethanol is known to be oxidized by alcohol dehydrogenase in the gastric mucosa, whereas Lin et al [16] have identified that cyclosporine is re-transferred from the enterocyte into the intestinal lumen by P-glycoprotein (an ATP-dependent xenobiotic transporter) and is also hydroxylated by cytochrome P450 (CYP3A4) in these cells. Morphine on the other hand is glucuronidated in intestinal mucosa and liver, and manganese is taken up from the portal blood into liver and excreted into bile.…”
Section: Discussionmentioning
confidence: 99%
“…Agents like ethanol, cyclosporine, and morphine have been identified to be so affected, in which the GI mucosa and the liver remove a significant portion of a toxicant during its passage through these tissues, thereby reducing its systemic availability. According to Lim et al[15], ethanol is known to be oxidized by alcohol dehydrogenase in the gastric mucosa, whereas Lin et al [16] have identified that cyclosporine is re-transferred from the enterocyte into the intestinal lumen by P-glycoprotein (an ATP-dependent xenobiotic transporter) and is also hydroxylated by cytochrome P450 (CYP3A4) in these cells. Morphine on the other hand is glucuronidated in intestinal mucosa and liver, and manganese is taken up from the portal blood into liver and excreted into bile.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in (34), failure due to pharmacodynamic and toxicological issues is of major concern. To be supportive, physiologically based pharmacokinetic models should provide interfaces for pharmacodynamic or toxicological models (19).…”
Section: Discussionmentioning
confidence: 99%
“…The equations (3)- (6) can easily be extended, e.g. to account for active transport processes (19,20), linear-or nonlinear metabolism (20,21), binding to other relevant molecules (20,22), including target molecules (19) and downstream effects. This opens the door for a wide range of applications in pharmacokinetics and -dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations